2017
DOI: 10.1080/00365513.2017.1402363
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and nodular thyroid diseases

Abstract: Nodular thyroid diseases are common in Turkey. Insulin resistance (IR) is considered as the most important component of metabolic syndrome (MetS), and it is thought to directly affect thyroid diseases, together with other components of MetS. The aim of this study was to evaluate potential factors associated with thyroid nodularity. This study was part of the prospective MELEN study. In total, randomly selected 2233 subjects were evaluated. A euthyroid subgroup of participants (n = 1432) was selected and 421 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
6
8
1
2
Order By: Relevance
“…In agreement with previous studies (16,17), the cross-sectional part of the present study demonstrated that nodular thyroid disease was more common in MetS patients, and that older age, female gender, and MetS presence were independent factors affecting TN occurrence. In addition, men with chronic MetS have an increased risk of TNs compared with those consistently free from MetS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (16,17), the cross-sectional part of the present study demonstrated that nodular thyroid disease was more common in MetS patients, and that older age, female gender, and MetS presence were independent factors affecting TN occurrence. In addition, men with chronic MetS have an increased risk of TNs compared with those consistently free from MetS.…”
Section: Discussionsupporting
confidence: 93%
“…Although several reports have demonstrated an association of MetS with TNs, they were mainly cross-sectional studies designed to evaluate either the prevalence of MetS in individuals with TNs vs. controls (12)(13)(14)(15), or, conversely, the prevalence of TNs in MetS patients (16,17). Meanwhile, related prospective studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that thyroid nodule is closely related to hypertension, BMI, and metabolic syndrome [11,43]. Our results showed that the prevalence of thyroid nodules in the patients with hypertension, BMI, and metabolic syndrome groups was higher than that in the control group, but no association was found between hypertension, BMI, metabolic syndrome, and thyroid nodules.…”
Section: Discussioncontrasting
confidence: 46%
“…Further, some authors indicated that thyroid volume are associated with iodine deficiency and supply, Body Mass Index, gender, age, cigarettes smoking, genetic factors, FBG and T2DM severity (Bener et al, 2009;Duran et al, 2014;Kir et al, 2018;Rezzonico et al, 2008;Bener et al, 2018). The current study is consistent with earlier reported the correlation between metabolic disorders characterized by insulin resistance and the risk of thyroid cancer (Marrero, 2010;Ghazali et al, 2010;Chen et al, 2010;Kir et al, 2018;Bener et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, T2DM and thyroid dysfunction are highly correlated as the two commonest endocrinological medical conditions reported in clinical practice (Akbar et al, 2006;Marrero, 2009;Papazafiropoulou et al, 2010;Ghazali & Abbiyesuku, 2010;Wang et al, 2015;Centeno Maxzud et al, 2016;Sarfo-Kantanka et al, 2017;Malaguarnera et al, 2017). Further, some authors indicated that thyroid volume are associated with iodine deficiency and supply, Body Mass Index, gender, age, cigarettes smoking, genetic factors, FBG and T2DM severity (Bener et al, 2009;Duran et al, 2014;Kir et al, 2018;Rezzonico et al, 2008;Bener et al, 2018). The current study is consistent with earlier reported the correlation between metabolic disorders characterized by insulin resistance and the risk of thyroid cancer (Marrero, 2010;Ghazali et al, 2010;Chen et al, 2010;Kir et al, 2018;Bener et al, 2018).…”
Section: Discussionmentioning
confidence: 99%